THE THIRD SPACE AND THE ROLE OF BUNDO KANDUANG IN RUMAH GADANG - Rosalinda Wiemar; Yasraf Amir Piliang; Deddy Wahjudi; Ruly Darmawan (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Minangkabau is a tribe in West Sumatra with a matrilineal kinship system, which draws lineage based on the mother's ethnicity. Therefore, women are the main characters in the tribe. Minangkabau women who are married, wise, and elder are called Bundo Kanduang, who have duties and obligations to carry out. Given the importance of the role of Bundo Kanduang, it is necessary to know how the role of Bundo Kanduang can be carried out in the Rumah Gadang, both physically/real and non-physical/imaginary. The research method used is an ethnographic method with a qualitative analysis approach using the theory of the third space from Edward Soja. Based on the analysis, it was found that the activities of Bundo Kanduang in carrying out its role have been facilitated in the Rumah Gadang, both physically and non-physically, even beyond what is known as third space.